Traditional use and conservation of the “calaverita” Laelia anceps subsp. dawsonii f. chilapensis Soto-Arenas at Chilapa, Guerrero, México - Salazar-Rojas, Víctor (2015)
Mexico lodges a heritage of traditional knowledge on use, management and conservation of a great vari- ety of genetic resources tie to its culture and idiosyn- crasy (Davis et al. 1994; Toledo 1991). That heritage is protected in the memory of the indigenous and rural villages of the country, which by means of the daily practice and oral transmission of their customs, have allowed several species to survive, among them some orchids of the genus Laelia (Halbinger and Soto 1997, Toledo 1991).